(untitled) (Journal of actual problems of jurisprudence, 2019)
This article is devoted to the issue of respect for the interests of coastal states in determining the legal regime of the regional seas. In particular, the author shows specificity of the legal regime of the regional seas by the example of Black Sea, makes conclusions about the need to resolve the status of such seas exclusively by the coastal states, considering a number of universally accepted treaty and customary norms of international maritime law.